The Chinese customers and service staff interactive affective system (CCSIAS): introduction to a multimodal stimulus dataset - Liu, Ping; Zhang, Yi; Xiong, Ziyue; Gao, Ying (Frontiers in Psychology, 2024)
To research the emotional interaction between customers and service staff, single-modal stimuli are being used to activate subjects' emotions while multimodal emotion stimuli with better efficiency are often neglected. This study aims to construct a multimodal emotion stimuli database (CCSIAS) with video records of real work status of 29 service staff and audio clips of interactions between customers and service staff by setting up wide-angle cameras and searching in company's Ocean Engine for 15 consecutive days. First, we developed a tool to assess the emotional statuses of customers and service staff in Study 1. Second, 40 Masters and PhD students were invited to assess the audio and video data to evaluate the emotional states of customers and service staff in Study 2, using the tools developed in Study 1. Third, 118 participants were recruited to test the results from Study 2 to ensure the stability of the derived data. The results showed that 139 sets of stable emotional audio & video data were constructed (26 sets were high, 59 sets were medium and 54 sets were low). The amount of emotional information is important for the effective activation of participants' emotional states, and the degree of emotional activation of video data is significantly higher than that of the audio data. Overall, it was shown that the study of emotional interaction phenomena requires a multimodal dataset. The CCSIAS (https://osf.io/muc86/) can extend the depth and breadth of emotional interaction research and can be applied to different emotional states between customers and service staff activation in the fields of organizational behavior and psychology.